Esterase 6 in Drosophila melanogaster: reproductive function of active and null males at low temperature. - Gilbert, D G (1982)
Esterase 6 is a polymorphic carboxylesterase (carboxylic-ester hydrolase, EC 3.1.1.1) localized to the reproductive tract of male Drosophila melanogaster and transferred to females at copulation. The reproductive fitness of males is strongly affected by temperature and the esterase 6 alleles (active versus null) that they carry. Low temperature (18 degrees C) dramatically changes the character of reproductive functions relative to optimal 25 degrees C. Males with active esterase 6 mate sooner, copulate for a shorter time, and produce more progeny per mating than do esterase 6 null males at 18 degrees C, in contrast to equal progeny production at 25 degrees C. A male esterase 6 effect on the remating speed of females at 25 degrees C is absent at 18 degrees C. Previous work suggests that male esterase 6 promotes ejaculate transfer, sperm storage, and use in females. The differences in reproductive fitness at 18 degrees C noted here may follow from the effects of esterase 6 on sperm transfer and utilization. The esterase 6 effect on productivity is consistent for different female types, even though the components of productivity that were affected, egg laying and egg fertility, changed with female type. These data lead to the hypothesis that the wide-spread polymorphism for esterase 6 may be adaptively significant.